2016
DOI: 10.1530/ec-15-0114
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of human follicular thyroid cancer cell lines in preclinical mouse models

Abstract: Follicular thyroid cancer (FTC) is the second most common type of thyroid cancers. In order to develop more effective personalized therapies, it is necessary to thoroughly evaluate patient-derived cell lines in in vivo preclinical models before using them to test new, targeted therapies. This study evaluates the tumorigenic and metastatic potential of a panel of three human FTC cell lines (WRO, FTC-238, and TT1609-CO2) with defined genetic mutations in two in vivo murine models: an orthotopic thyroid cancer mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…While the xenograft models are quite straightforward in that the cells grown and collected are injected into the subcutaneous tissues of immunocompromised mice, the orthotopic model is more complex to establish, since it requires a microsurgical procedure to directly place the cells into one or both the thyroid lobes [ 32 , 33 , 34 ]. Nonetheless, since the development of such a model [ 35 ], orthotopic implantation has been widely adopted to study the genetic and bio-molecular patterns of thyroid carcinogenesis [ 9 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ].…”
Section: Mouse Models Of Thyroid Cancersmentioning
confidence: 99%
See 1 more Smart Citation
“…While the xenograft models are quite straightforward in that the cells grown and collected are injected into the subcutaneous tissues of immunocompromised mice, the orthotopic model is more complex to establish, since it requires a microsurgical procedure to directly place the cells into one or both the thyroid lobes [ 32 , 33 , 34 ]. Nonetheless, since the development of such a model [ 35 ], orthotopic implantation has been widely adopted to study the genetic and bio-molecular patterns of thyroid carcinogenesis [ 9 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ].…”
Section: Mouse Models Of Thyroid Cancersmentioning
confidence: 99%
“…Even if the orthotopic model closely resembles the original biological tumor’s behavior in term of local invasion and metastasis [ 35 , 36 , 37 , 40 ], particularly when aggressive ATC cells are used, other specific models have been developed to study metastasis [ 32 , 45 ]. Furthermore, in the orthotopic mouse models, the local invasion of neck tissues by the primary tumor can lead to animal suffering, due to the inability to swallow or breath properly; thus, there might not be enough time for the development of metastasis [ 39 , 40 ].…”
Section: Mouse Models Of Thyroid Cancersmentioning
confidence: 99%
“…In general, differentiated thyroid cancers (DTC), including PTC and FTC, tend to be biologically indolent, highly curable and has an excellent prognosis [Leonardi et al, ; Reeb et al, ]. The initial standard medical treatment for DTC after thyroidectomy is radioiodine ablation with (conventional therapy) or without thyroid hormone suppression therapy (use of recombinant human thyrotropin, rhTSH) [Pacini and Castagna, ; Zanotti‐Fregonara et al, ; da Silva et al, ].…”
Section: Introductionmentioning
confidence: 99%
“…The first characterization of WRO cell was documented by Estour et al [] who evaluated the effect of external radiation by 60 Co in a single dose of 10 Gy. Reeb et al [] demonstrated that they were the most tumorigenic and metastatic of the three human FTC cell lines (WRO, FTC‐238, TT 2609‐CO2) analyzed in xenotransplantation assays in immunodeficient mice.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation